Learning a foreign language understanding the fundamentals of linguistics - Poole, Alex (Rowman & Littlefield Publishers, 2020)
"This book introduces aspiring bilinguals to second language acquisition research, but in a way that is accessible to non-specialists and relevant to their lives as language learners"--